Transanal ileoproctostomy is feasible in human cadavers. (October 2014) - Polese, L.; Lezoche, E.; Porzionato, A.; Lezoche, G.; Da Dalt, G.; Macchi, V.; Stecco, C.; De Caro, R.; Norberto, L.; Merigliano, S.
Abstract Aim An ileorectal bypass performed entirely through a transanal route has recently been described in an animal model. The present study aimed to demonstrate its technical feasibility in four human cadavers. Method A transanal endoscopic microsurgery (TEM) device and endoscopic instruments were used. The principal steps of the procedure included insertion of the TEM device, rectostomy above the peritoneal reflection, peritoneoscopy using a standard gastroscope and delivery of the small bowel through the proctostomy to perform an anastomosis. Results The procedure was successfully completed using transanal access in all cases. The mean procedure time was 90 min. The bypass was patent, and the anastomosis between the intraperitoneal rectum and the terminal ileum was leakproof. Conclusion Transanal ileoproctostomy is technically feasible in human cadavers. The procedure may become an alternative to stoma formation in selected patients with colonic obstruction.